2024
DOI: 10.1002/pen.26689
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and crystallization properties of hot runner injection molded virgin and recycled polypropylene

Nicholas Bowen,
Cameron Guyer,
Terence Rippon
et al.

Abstract: As the demand for sustainable and environmentally conscious practices continues to grow, recycled plastics have become increasingly popular for plastics manufacturers. However, reprocessing these materials can result in inconsistencies in both process and product quality, leading to a loss in mechanical properties. To address this issue, this work investigates the injection molding of recycled and virgin polypropylene (PP). Using a multi‐cavity hot runner mold, correlations between processing parameters, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Shear-induced processing techniques have been extensively investigated with other polymer materials, such as PP and PE [ 152 , 154 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ]. For example, previous research from the authors showed that for PP, by increasing melt and decreasing mold temperatures, polymer chains aligned and froze with higher orientation, forming β crystals [ 163 ]. However, there is a conspicuous absence of studies concerning shear-induced technology applied to PLA and its blends.…”
Section: Processing Optimization Techniquesmentioning
confidence: 99%
“…Shear-induced processing techniques have been extensively investigated with other polymer materials, such as PP and PE [ 152 , 154 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ]. For example, previous research from the authors showed that for PP, by increasing melt and decreasing mold temperatures, polymer chains aligned and froze with higher orientation, forming β crystals [ 163 ]. However, there is a conspicuous absence of studies concerning shear-induced technology applied to PLA and its blends.…”
Section: Processing Optimization Techniquesmentioning
confidence: 99%